Thermal stress alters expression of genes involved in one carbon and DNA methylation pathways in Atlantic cod embryos - Skjærven, Kaja H.; Hamre, Kristin; Penglase, Samuel; Finn, Roderick Nigel; Olsvik, Pål A. (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2014)
One-carbon (1-C) metabolism is essential for normal embryonic development through its regulation of DNA methylation and cell proliferation. With consideration to the potential future anthropogenic oceanic warming, we studied the effects of both acute thermal stress and continuous thermal stress (10°C) during Atlantic cod embryo development on the expression levels of genes associated with the 1-C metabolism, including DNA methyltransferases. We conducted a phylogenetic analysis of vertebrate DNA methyltransferases to determine the number and similarity of DNMT found in Atlantic cod. This analysis revealed that Atlantic cod have one maintenance dnmt (dnmt1) and five de novo DNMTs (dnmt4, dnmt3, dnmt3b, dnmt3aa, dnmt3ab). Stage specific changes in expression levels occurred for all genes analyzed. The effect of acute thermal stress was evaluated during early development. Compared to controls these experiments showed significant alterations in expression levels of several genes, that in some instances were reversed at later stages of development. A significant effect of continuous thermal stress was found in gastrula embryos where lower mRNA expression levels of 1-C metabolism, de novo DNMTs and cell proliferation genes were detected. One exception was the maintenance DNMT, which was only sensitive to acute and not continuous thermal stress. DNA methylation status indicated that blastula embryos were hypomethylated compared to spermatozoa and late gastrula stages. In post-gastrula stage, however, continuous thermal stress resulted in a higher degree of DNA methylation compared to controls. These data reveal that the regulation of epigenetically important transcripts in the 1-C metabolism of Atlantic cod embryos is sensitive to thermal stress.